2021
DOI: 10.31234/osf.io/2jksg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negativity bias in the spread of voter fraud conspiracy theory tweets during the 2020 US election

Abstract: During the 2020 US presidential election, conspiracy theories about large-scale voter fraud were widely circulated on social media platforms. Given their scale, persistence, and impact, it is critically important to understand the mechanisms that caused these theories to spread so rapidly. The aim of this study was to investigate whether retweet frequencies among proponents of voter fraud conspiracy theories on Twitter during the 2020 US election are consistent with frequency bias, demonstrator bias, and/or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…For understanding online misinformation, a key factor should be how β and J act upon the sharing of information that are explicitly labelled by popularity (likes) as well as varying micro-levels of intrinsic utility, iterated over thousands/millions of online actions [61,124]. The interaction between β and J indicates a reason why culture with massive numbers of users (large J and N, low β) arguably change continually without necessarily getting 'better' [61,66,91,[138][139][140]. Additionally, the homophily under conformity in the model resembles the well-known sorting and polarization in social media and politics [129,134,135,141].…”
Section: Discussionmentioning
confidence: 99%
“…For understanding online misinformation, a key factor should be how β and J act upon the sharing of information that are explicitly labelled by popularity (likes) as well as varying micro-levels of intrinsic utility, iterated over thousands/millions of online actions [61,124]. The interaction between β and J indicates a reason why culture with massive numbers of users (large J and N, low β) arguably change continually without necessarily getting 'better' [61,66,91,[138][139][140]. Additionally, the homophily under conformity in the model resembles the well-known sorting and polarization in social media and politics [129,134,135,141].…”
Section: Discussionmentioning
confidence: 99%
“…While research within cultural evolution often focuses on the role of context biases in transmission, recent research suggests that content biases are as influential, or more influential than context biases on the selection (Acerbi & Tehrani, 2018), faithful transmission (Berl et al, 2021) and wider dissemination of information (Youngblood et al, 2021). Here research examining content biases is reviewed, with a focus on considering these biases across three phases of transmission: choose-to-receive, encode-and-retrieve, and choose-to-transmit.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Some research suggests a general advantage for more emotionally arousing content online (Brady, Wills, Jost, Tucker, & Bavel, 2017;Stieglitz & Dang-Xuan, 2013; but see critiques in; Burton, Cruz, & Hahn, 2021). Other research suggests an advantage for negative content, finding evidence for negativity in online "fake news" articles (Acerbi, 2019), within online "echo chambers" (Asatani, Yamano, Sakaki, & Sakata, 2021;Del Vicario et al, 2016), in tweets about political events (Bellovary, Young, & Goldenberg, 2021;de León & Trilling, 2021;Schöne, Parkinson, & Goldenberg, 2021), in tweets about electoral conspiracy theories (Youngblood et al, 2021) and in tweets about a climate change summit (Hansen, Arvidsson, Nielsen, Colleoni, & Etter, 2011). However, this is not universal, other research has found evidence for positivity bias in the sharing of news content on social media (Bakshy, Hofman, Mason, & Watts, 2011;Trilling, Tolochko, & Burscher, 2017).…”
Section: Emotion Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…A byproduct of this coevolution is that major changes in collective structure can reduce the adaptiveness of social learning strategies. In global and interconnected online communities, tendencies to defer to prestige or attend to negative messages might enhance the spread of misinformation or conspiracy theories (Acerbi, 2016;Youngblood et al, 2021). In declining animal species with learned migration and foraging routes, tendencies to conform might reduce their ability to respond to human-induced environmental changes (Barrett et al, 2019).…”
Section: Culture As Collective Intelligencementioning
confidence: 99%